The Reception of Wilhelm Humboldtʼs Ideological Legacy by Ukrainian Scientists in the Context of the Ukrainain Language Development and Language Education Problem in the ХІХ – Early ХХ Century - Anna Kryshko (Pedagogical Discourse, 2013)
The historiographical review of the research literature related to the diverse reception of Wilhelm Humboldtʼs ideological legacy by Ukrainian scientists is carried out. The scientific literature that lighted up the question of development of Ukrainian and position of linguistic education in the difficult terms of political separation of Western and Eastern Ukraine in the nineteenth – early twentieth century is analyzed. The most significant Ukrainian scientific and historical works that reveal Wilhelm Humboldtʼs pedagogical and linguistic views are presented.